NAFLD polygenic risk score and risk of hepatocellular carcinoma in an East Asian population. Issue 9 (3rd May 2022) - Thomas, Claire E.; Diergaarde, Brenda; Kuipers, Allison L.; Adibi, Jennifer J.; Luu, Hung N.; Chang, Xuling; Dorajoo, Rajkumar; Heng, Chew‐Kiat; Khor, Chiea‐Chuen; Wang, Renwei; Jin, Aizhen; Koh, Woon‐Puay; et al.
Abstract: It is difficult to identify people with nonalcoholic fatty liver disease (NAFLD) who are at high risk for developing hepatocellular carcinoma (HCC). A polygenic risk score (PRS) for hepatic fat (HFC‐PRS) derived from non‐Asians has been reported to be associated with HCC risk in European populations. However, population‐level data of this risk in Asian populations are lacking. Utilizing resources from 24, 333 participants of the Singapore Chinese Health Study (SCHS), we examined the relationship between the HFC‐PRS and HCC risk. In addition, we constructed and evaluated a NAFLD‐related PRS (NAFLD‐PRS) with HCC risk in the SCHS. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) of HCC incidence with both HFC‐PRS and NAFLD‐PRS. The HFC‐PRS and NAFLD‐PRS were highly correlated (Spearman r = 0.79, p < 0.001). The highest quartiles of both the HFC‐PRS and the NAFLD‐PRS were associated with significantly increased risk of HCC with HR of 2.39 (95% CI 1.51, 3.78) and 1.77 (95% CI 1.15, 2.73), respectively, compared with their respective lowest quartile. Conclusion: The PRS for hepatic fat content or NAFLD may be useful for assessing HCC risk in both Asian and European populations. The findings of this and prior studies support a potential causal role of genetically determined NAFLD in HCC development. Abstract : It is difficult to identify people with non‐alcoholic fatty liver disease (NAFLD) who are at high risk for developing hepatocellular carcinoma (HCC). We examined if two polygenic risk scores: HFC‐PRS (hepatic fat), derived in a mixed ancestry American population and previously validated in Europeans; and NAFLD‐PRS, which we calculated utilizing East Asian populations, were associated with HCC risk in our East Asian population in the Singapore Chinese Health Study. Higher levels of both HFC‐PRS and NAFLD‐PRS were associated with higher risk of HCC, and both may be useful assessing HCC risk in Asian and European populations.image